1989
DOI: 10.1016/0309-1651(89)90137-9
|View full text |Cite
|
Sign up to set email alerts
|

Scanning and transmission electron microscopy of biodegradable microspheres (DSM) in blood vessels

Abstract: A type of biodegradable microsphere (DSM), approximately 45 microns in diameter, made of polymerized potato starch (Pharmacia, Sweden) was intravenously injected into rats to observe the state of DSM in small blood vessels in the kidney and liver at the electron microscopic level. Prior to their digestion with amylase, individual DSM changed their round shape to an irregularly folded one to occupy almost the whole area of the lumen. At the transmission electron microscopic level, DSM were impregnated with coll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

1989
1989
2007
2007

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…Thus, in a global ischemia model, Yoshizumi et al [ 40 ] found that 15 or 30 minutes global ischemia made little difference to BBB disruption when measured after reperfusion for 3 or 6 hours. On the other hand, Sampaolo et al [ 19 ] did observe differences in the distribution pattern of ionic lanthanum following 15, 30, or 60 minutes middle cerebral artery occlusion, but did not observe extravasation of the larger molecular weight tracers HRP or Evan's Blue. The permeability values of the present experiments are of a similar order to that reported for global ischemia experiments (albumin K in ∼ 9 ml·g −1 ·s −1 following 20 minutes global ischemia followed by 2 hr reperfusion; [ 37 ]) and are considerably higher than after 2 hours MCAO (PS ∼ 0.44 ml·g −1 ·s −1 calculated from [ 32 ]).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Thus, in a global ischemia model, Yoshizumi et al [ 40 ] found that 15 or 30 minutes global ischemia made little difference to BBB disruption when measured after reperfusion for 3 or 6 hours. On the other hand, Sampaolo et al [ 19 ] did observe differences in the distribution pattern of ionic lanthanum following 15, 30, or 60 minutes middle cerebral artery occlusion, but did not observe extravasation of the larger molecular weight tracers HRP or Evan's Blue. The permeability values of the present experiments are of a similar order to that reported for global ischemia experiments (albumin K in ∼ 9 ml·g −1 ·s −1 following 20 minutes global ischemia followed by 2 hr reperfusion; [ 37 ]) and are considerably higher than after 2 hours MCAO (PS ∼ 0.44 ml·g −1 ·s −1 calculated from [ 32 ]).…”
Section: Discussionmentioning
confidence: 98%
“…Degradable starch microspheres have been used in chemotherapeutic drug administration for hepatic cancer [ 16 ] but have not been widely used as emboli to produce reversible ischemia. An electron microscopy study of the progress of microsphere emboli showed that they changed shape and occupied almost the whole of the microvascular lumen while they were acted on by plasma amylase [ 19 ], and it has been shown that irreversible brain damage results from starch microsphere injection [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…Where they have been used previously to occlude the rat cerebral vasculature, it was found that the irreversible damage was related to the number of microspheres injected ( Laccourreye et al ., 1993 ). An electron microscopy study of starch microsphere interaction with rat liver and kidney microvessels showed that they changed shape and occupied almost the whole of the lumen before being digested by plasma amylase ( Makita et al ., 1989 ). We found that blocking TRPV1 with capsazepine during experimental focal cerebral ischaemia–reperfusion reduced the blood–brain barrier disruption considerably.…”
Section: Discussionmentioning
confidence: 99%